South-facing elevation of the Mandaleshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the south-facing elevation of the Mandaleshwar Mahadev Temple. The temple’s plan consists of a mukhamandapa (front porch) followed by a mandapa (pillared hall), an antarala (antechamber), and a garbhagriha (sanctum sanctorum). The mandapa is semi-open, that is, having lateral wings or transepts on the south and north sides. The original shikhara (superstructure) of the temple is probably lost. Presently, the temple has a shekhari (multi-spired) variety of shikhara built in brick.